PRACTICAL TRAINING OF OFFICERS OF THE STATE FIRE SERVICE THROUGH GAME-BASED LEARNING - V. V. Bulgakov; A. A. Lazarev; E. P. Konovalenko; T. A. Mochalova (Russian State Vocational Pedagogical University, 2019)
Introduction. It is common knowledge that lives and health of people as well as safe operation of various infrastructures depend on the high level of professionalism of the staff responsible for safety. It fully belongs to the personnel structure of the State Fire-Fighting Service (SFFS) of the Emergency Control Ministry (EMERCOM) of Russia. However, in a technologically developed society, there is a contradiction between the increased requirements to young officers' competencies and the impossibility to achieve a proper complex of graduates' characteristics by providing education through only standard traditional techniques, which continue to be prevalent in higher education and ensure optimisation of professional activity in general.The aim of the present publication was to present the developed methodology of game-based learning for training of cadets of educational organisations of higher education of the EMERCOM of Russia. The methodology is designed to develop cadets' practical skills in the field of rescue operations and firefighting.Methodology and research methods. In the course of the research, the methods of system analysis, synthesis and modelling of professional activity were employed. The research is based on the provisions of the associative-reflex theory, the theory of motivation development and the theory of contextual, modular, problem-based, reflexive and game-based learning.Results and scientific novelty. The interrelated elements of the pedagogical theories and didactic principles, united by a common scientific-methodological objective, allowed the authors to create a methodological tool for gradual formation and consolidation of organisational and administrative competencies of young officers of the State Fire-Fighting Service. The authors considered monitoring indicators of the results of training of graduates of Ivanovo Fire and Rescue Academy in order to develop the methodology, which purposefully addresses the shortcomings and gaps of education of future firefighters' knowledge and their practical skills.The competitive spirit increases positive dynamics of the educational process and contextual content of business games, built on realistic situations from the field of firefighting and implementation of rescue operations at various socioindustrial, housing and transport infrastructures, attract interest of cadets and stimulate their motivation to improvement of own business qualities. The advantages of the offered methodology are the following: the possibility to design various schemes of practical training through the modular principle of their design; the development in cadets of the skills of team interaction, acquisition of professional experience by them in the process of role performance of duties of chiefs of rescue and fire fighting offices and department guards; the readiness formation to quickly adapt to new circumstances and to cope with non-standard problems in the conditions of limited time; to develop the abilities of critical thinking in young officers, to reflect own activity and to define the directions of professional growth.Practical significance. The proposed methodology demonstrated its effectiveness and practical importance for cadets' training in the field of rescue and firefighting, as confirmed by, inter alia, the improvement of academic performance in special disciplines. The proposed methodological tool has shown promise in more rational redistribution of teaching time and expansion of the base of practical modules for designing business games for the purpose of development of new relevant professional competencies in students.